47.5k views
0 votes
-3(-4 - 6y) +7 (-y + 5) = -8. What is the answer for y?

2 Answers

4 votes

Answer:

y=3.18 repeting

Explanation:

You first simplify what was in the parentheses giving you 12+18y-7y+35=-8

You then combine like terms giving you 11y+47=-8

You then subtract 47 from both sides giving you 11y=-35

Finally you divide both sides by 11 giving you the answer 3.18 repeating

I can't put the correct notation on here but basically you put a little line over .18 and that shows that it repeats for infinity

User CWBudde
by
5.1k points
4 votes

Answer:

y = -5

Explanation:

-3(-4-6y) + 7(-y + 5) = -8

12 + 18y -7y + 35 = -8

35 + 12 + 18y-7y = -8

47 + 11y = -8

-47. + 11y = -8-47

11y = -55

11y/11 = -55/11

y = -5

User Michael S Priz
by
5.2k points